Strategi Pemasaran untuk Meningkatkan Penjualan Pupuk Organik (Studi Kasus pada Simantri 174 Gapoktan Dharma Pertiwi Kelurahan Lukluk, Kecamatan Mengwi, Kabupaten Badung) - PRANITI, NI LUH GEDE WULAN ADI; PARINING, NYOMAN; PUTRA, I GEDE SETIAWAN ADI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2016)
Abstract Marketing Strategies to Increase Sales Organic Fertilizer (Case Study on 174 Simantri Gapoktan Dharma Pertiwi LuklukVillage, District Mengwi, Badung ) The marketing strategy is a form of plan that decompose in the field of marketing. To obtain optimal results, marketing strategies have a board scope in the field of marketing include the strategy in the face of competition, pricing strategy, product strategy, service strategy.This study aims to determine the general strategy alternative strategies for marketing organic fertilizer at 174 SimantriGapoktan Dharma Pertiwi. This study was conducted in July 2015 held at 174 SimantriGapoktan Dharma Pertiwi Lukluk Village, District Mengwi, Badung. The analytical method used in this research is the analysis of the corporate environment that consists of a matrix of IFAS (Internal Strategic Factors) and matrix analysis EFAS (External Strategic Factors), matrix IE (internal external), and SWOT matrix. Analysis of IE matrix based on the score matrix IFAS and matrix EFAS to obtain the position of the business of Simantri 174 Gapoktan Dharma Pertiwi in internal conditions are very strong and the response effort organic fertilizer is to external factors that it faces is high. Swot matrix analysis resulted in several alternative strategies, strategy ST three generate alternative strategies, WO strategy resulted in four alternative strategiesand strategies WT produce three alternative strategies.   Keywords :marketing strategy, organic fertilizer, analytical method